Adaptive pulse impressed current cathodic protection using fuzzy logic control - Raditya Burhani Assidqi; Mohd Rafi Adzman; Shaiful Rizam Shamsudin; Karisma Trinanda Putra; Aiman Arif Mohd Sollehuddin (Institute of Advanced Engineering and Science, 2026)
Corrosion in buried metal infrastructure poses significant economic and safety risks, requiring advancements over traditional impressed current cathodic protection (ICCP). This study presents an innovative pulse impressed current cathodic protection (PICCP) system integrating high- frequency pulse feeding with fuzzy logic control (FLC) for enhanced stability and energy efficiency. Utilizing an Arduino Uno and ESP8266 for real-time IoT monitoring via Blynk, the system was tested for 14 days in humus soil (10–20 kilo-ohm·cm, pH 5–6). Results demonstrate that PICCP consistently maintained off-potentials within the safe range of –1100 to –850 mV, whereas conventional ICCP failed by the eighth day, falling below – 750 mV. The adaptive PICCP system, operating between 44–52 kHz, achieved a tenfold improvement in energy efficiency, requiring only 0.74– 0.80 mA compared to 9–10 mA for ICCP. These findings validate the PICCP framework as a robust, scalable solution for embedded metallic infrastructures, effectively combining automated remote monitoring with adaptive electrochemical protection.